This preview shows page 1. Sign up to view the full content.
Unformatted text preview: has the same base a with an exponent equal to the sum of the exponents of the multiplicands. An example is: x 4 * x 5 = x 4+5 = x 9 . The second rule is the power rule, which says that (a m ) n = a mn . In words, we keep the base unchanged and multiply the exponents. An example is: (x 3 ) 2 = x 6 . With rational (fractional) exponents, these two rules work exactly the same way. For example, if were performing the multiplication: * = . * . = = 5 5 50 5 50 5 51 5 A third expression to simplify is: 8 (-5/3)...
View Full Document
- Spring '10